Galectin 3 expression in regional lymph nodes and lymph node metastases of oral squamous cell carcinomas - Wehrhan, Falk; Büttner-Herold, Maike; Distel, Luitpold; Ries, Jutta; Möbius, Patrick; Preidl, Raimund; Geppert, Carol-Immanuel; Neukam, Friedrich Wilhelm; Kesting, Marco Rainer; Weber, Manuel (BMC Cancer, 2018)
BACKGROUND: Neck dissection is standard in surgical management of oral squamous cell carcinomas (oscc). However, the immunologic link between primary tumor and lymph nodes is insufficiently understood. Galectin 3 (Gal3) promotes M2 polarization of macrophages and contributes to immunosuppression. The current study analyzes the association between Gal3 expression in regional lymph nodes of oscc with histomorphologic parameters (T-, N-, L- Pn-stage, grading) of the primary tumor. Additionally, Gal3 expression is correlated with markers of macrophage polarization (M1 vs. M2). METHODS: Preoperative diagnostic biopsies (n = 26), tumor resection specimens (n = 34), tumor-free lymph nodes (n = 28) and lymph node metastases (n = 10) of T1/T2 oscc patients were immunohistochemically analyzed for Gal3 and macrophage marker (CD68, CD11c, CD163 and MRC1) expression. The number of positive cells and the expression ratios were quantitatively assessed. RESULTS: High Gal3 expression in tumor-free regional lymph nodes was significantly (p < 0.05) associated with increased tumor size. The epithelial compartment of lymph node metastases showed a significantly (p < 0.05) increased Gal3 expression compared to biopsies and tumor resection specimens. Cell density of M2 macrophages was significantly (p < 0.05) and positively correlated with the number of Gal3 expressing cells in lymph nodes and tumor specimens. CONCLUSION: Gal3 expression in regional lymph nodes might be associated with oscc progression. The increased Gal3 expression in regional lymph nodes of larger tumors underlines the need of immunomodulatory treatment concepts in early-stage oscc. Blocking of Gal3 might be a therapeutic option in oral cancer.
EVALuna2:34900